Chapter 9 Moral Responsibility and the Justification of Policies to Preserve Antimicrobial Effectiveness - Giubilini, Alberto (Springer Nature, 2020)
Restrictive policies that limit antimicrobial consumption, including therapeutically justified use, might be necessary to tackle the problem of antimicrobial resistance. We argue that such policies would be ethically justified when forgoing antimicrobials constitutes a form of easy rescue for an individual. These are cases of mild and self-limiting infections in otherwise healthy patients whose overall health is not significantly compromised by the infection. In such cases, restrictive policies would be ethically justified because they would coerce individuals into fulfilling a moral obligation they independently have. However, to ensure that such justification is the strongest possible, states also have the responsibility to ensure that forgoing antimicrobials is as easy as possible for patients by implementing adequate compensation measures.